Glioblastoma Vasculature: From its Critical Role in Tumor Survival to Relevant in Vitro Modelling - Pacheco, Catarina; Martins, Cláudia; Monteiro, Joaquim; Baltazar, Fátima; Costa, Bruno M.; Sarmento, Bruno (Frontiers in Drug Delivery, 2022)
Biochemical and biophysical cues governing glioblastoma (GBM) progression are complex and dynamic. Tumor blood vessels, often recognized only by their transport functions, are more deeply involved in this process. Vessels are involved in tumor immune evasion, matrix alterations and stem cell stimulation, contributing for tumor treatment resistance and patients’ poor survival. Given blood vessel complex and dynamic nature, they are hardly represented in conventional GBM monolayered in vitro models. However, other in vitro approaches, such as three-dimensional (3D) models, incorporating extracellular matrix (ECM), malignant and stromal cells, and promoting their communication, can resemble neovascularization, growing blood vessels in a tumor-like microenvironment. These models mimic GBM physiological architecture and key biochemical and biophysical environments, allowing the investigation of the impact of vascularization in tumor progression. For researchers in neuro-oncology field, 3D vascularized GBM models are of great interest. They are promising tools to evaluate individual driven neovascularization and identify mediators involved in those processes. Moreover, they may be used to test potential anti-GBM therapies targeting blood vessels or influenced by them. This review will discuss the significance of blood vessels in GBM and review novel 3D pre-clinical vascular models.